2017
DOI: 10.4317/jced.54359
|View full text |Cite
|
Sign up to set email alerts
|

Severe tetracycline dental discoloration: Restoration with conventional feldspathic ceramic veneers. A clinical report

Abstract: The treatment of severe tetracycline discoloration is a challenge for the dentist. There are several treatment options and one of the most effective is the use of feldspathic veneers. The aim of this clinical case was to carry out the replacement with conventional feldspathic ceramic veneers on a patient with highly stained teeth (grade IV tetracycline) by a minimally invasive approach. Clinical examination revealed gingival retraction, color change of the veneers, ceramic cracked of 1.1 and 1.3 and incisal we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 11 publications
(22 reference statements)
1
10
0
2
Order By: Relevance
“…In the BAP group, 0.5 mm thick ceramic veneer (S1) resulted in a Δ E value not statistically significantly different than those obtained for 1 mm thick ceramic veneer (S2) of the three tested groups (NB, BBP, and BAP), which is in agreement with previous studies [ 13 , 29 ], as when the lightness of the substrate shade is increased, a higher Δ E value can be achieved from a thinner ceramic veneer combination.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the BAP group, 0.5 mm thick ceramic veneer (S1) resulted in a Δ E value not statistically significantly different than those obtained for 1 mm thick ceramic veneer (S2) of the three tested groups (NB, BBP, and BAP), which is in agreement with previous studies [ 13 , 29 ], as when the lightness of the substrate shade is increased, a higher Δ E value can be achieved from a thinner ceramic veneer combination.…”
Section: Discussionsupporting
confidence: 92%
“…In attempting to treat severely discolored teeth by veneering, there is a considerable risk that the dark shade of the tooth tissue substrate will shine through relatively thin and translucent ceramics. Therefore, several approaches have been used to mask the underlying color; these include employing more opaque ceramics and luting cement [ 8 10 ], increasing the preparation depth [ 11 ] to allow adequate space for the ceramic thickness [ 12 ], or manipulation of the prepared tooth to lighten its shade [ 13 ]. Each of these approaches has its problems.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that porcelain veneer was 28.35 ± 4.37% and all-ceramic crown was 56.93 ± 3.47%. The reduction in all-ceramic crown was significantly higher than that of the porcelain veneer (P < .05) which was a popular mean of correcting aesthetic because of the conservative amount of tooth structure that needs to be removed [16, 17]. Pearson correlation analysis suggested that there was no correlation between the two types of restoration (P> .05).…”
Section: Discussionmentioning
confidence: 99%
“…Diante disso, o uso de laminados cerâmicos, se constitui em uma importante opção. 12,13 Os laminados cerâmicos propiciam mínimo desgaste do dente, o que estabelece melhor estética, tornando-se uma boa opção para dentes manchados por tetraciclina e com uma má resposta ao branqueamento. Esses elementos dentários devem ser incialmente submetidos a um clareamento, a fim de diminuir as manchas, pois os laminados possuem pequena espessura.…”
Section: Discussionunclassified
“…A literatura aponta uma longevidade de 95,7% após 5 anos e 87% após 8 anos para esses materiais. 5,12,14 Tona-se necessário a habilidade do cirurgião-dentista no preparo dos dentes para recebimento de laminados cerâmicos, pois há exigência de treinamento prévio, assim como os procedimentos adesivos para cimentação são críticos e demorados.…”
Section: Discussionunclassified